ANALISIS KEMAMPUAN COMPUTATIONAL THINKING SISWA PADA MATERI ALJABAR DITINJAU DARI PEMECAHAN MASALAH MATEMATIS - Silvia, Rahmatika Diah; Pramasdyahsari, Agnita Siska; Nizaruddin (Universitas Insan Budi Utomo, 2023)
Many students still have difficulty solving problems related to mathematics, one of which is algebraic material. Computational thinking is an ability needed to assist students in solving problems faced by students through abstraction, pattern recognition, decomposition, and algorithm skills. This study aims to describe the computational thinking abilities of IX grade junior high school students in solving mathematical problem solving. This type of research is a qualitative descriptive research. The time for conducting research is in the odd semester of the 2022/2023 academic year. The subjects taken were IX A grade students at SMP Negeri 2 Karangrayung. Using the problem- solving ability test, 2 students with high-level problem-solving abilities, 2 students with medium-level problem-solving abilities, and 2 students with low-level problem-solving abilities were selected using the problem-solving ability test. The data collection techniques used were problem solving ability tests, computational thinking ability tests, and interviews. Data analysis techniques were carried out in 3 stages, namely data reduction, data presentation, and drawing conclusion. Data validity checking technique uses source triangulation. The results of this study show that students with high-level problem-solving skills are able to meet all indicators of computational thinking, students with medium- level problem-solving abilities are able to meet fulfill 3 of 4 computational thinking indicators, while students with low-level problem-solving skills are able to fulfill 2 of 4 computational thinking indicators.